Ocean Literacy and Knowledge Transfer Synergies in Support of a Sustainable Blue Economy - Fernández Otero, Rosa M.; Bayliss-Brown, Georgia A.; Papathanassiou, Martha (Frontiers in Marine Science, 2019)
Since 2011, when the first European ocean literacy (OL) project was launched in Portugal, the number of initiatives about this topic in Europe has increased notoriously and their scope has largely widened. These initiatives have drawn from the seven ‘Ocean Literacy Principles’ that were developed by the College of Exploration Ocean Literacy Network in 2005. They represent a source of inspiration for the many endeavours that are aiming to achieve a society that fully understands the influence of themselves - as individuals and as a population - on the ocean and the influence of the ocean on them. OL initiatives throughout the past years, globally, have resulted in the production of countless didactic and communication resources that represent a valuable legacy for new activities. The OL research community recognises the need to build up the scope of OL by reaching the wider Blue Economy actors such as the maritime industrial sector. It is hoped that building OL in this sector will contribute to the long-term sustainable development of maritime activities. The ERASMUS+ project ‘MATES’aims to address the maritime industries' skills shortages and contribute to a more resilient labour market. MATES’ hypothesis is that through building OL in educational, professional and industrial environments, it is possible to build a labour force that matches the skills demand in these sectors and increases their capacity to uptake new knowledge. The MATES partnership will explicitly combine OL and knowledge transfer by applying the ‘COLUMBUS Knowledge Transfer Methodology’ as developed by the H2020-funded COLUMBUS project.